Repository metrics and its role in research evaluation - Aguillo, Isidro F. (Anuario ThinkEPI, 2009)
Scientific repositories are playing a significant role in scholarly communication, mostly due to the success of open access initiatives. Quantitative indicators to describe their contents and evaluate their usage and impact have been developed. The Ranking Web of repositories is introduced as a webometrics tool to rank the top 200 academic repositories, including both thematic and institutional ones.